American economic review - American Economic Association.; American Economic Association. Meeting. Papers and proceedings of the ... Annual Meeting of the American Economic Association. (American Economic Association, 1911)
Merger of: Economic bulletin; American Economic Association quarterly.The American economic review, with its supplements, forms the 4th series of the Publications of the American Economic Association.Each vol. includes also: Papers and proceedings of the ... Annual Meeting of the American Economic Association.Includes annual List of doctoral dissertations in political economy in progress in American universities and colleges; and the Handbook of the American Economic Association. Includes bibliographical references.5-9 issues every year. With Papers and proceedings of the 1964, 1965, 1968, 1969, 1971 annual meeting of the American Economic Association.